Penerapan Model Pembelajaran Quantum Learning dengan Pendekatan Kontekstual untuk Meningkatkan Hasil Belajar Matematika - Afriani, Fera; Nalim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The main objective of this study is to determine whether there is an increase in student mathematics learning outcomes through the application of the Quantum Learning model with a contextual approach. This type of research is experimental research with a True Experimental Design research design in the form of a Pretest-Posttest Control Group Design. The research was conducted in two classes, namely class VIII A as the control class and class VIII B as the experimental class. The hypothesis test used is the Independent Sample T-Test, and concludes that with the acquisition of a significance result (2-tailed) of 0.033 <0.05, Ha is accepted, which means that there is an increase in student mathematics learning outcomes through the application of the Quantum Learning model with a contextual approach.